Solution Processing of Doped Indium Oxide for Applications as Transparent Conducting Oxides - Firmino, Rita Maria Gomes (2022)
Indium oxide (In2O3) has been widely used and studied as transparent conducting oxide (TCO). However, some of the more promising dopants for this oxide have not received much attention and even fewer explored by solution processes. This work focuses on developing solution processed doped (Hf, Mo, and Zr) In2O3 thin films and evaluating various annealing parameters on TCOs properties. Different processing syntheses, metallic cations molar ratio, and the number of deposited layers were studied, concluding that 0.2 M concentration and 8 layers deposition by spin coating using solution combustion synthesis (SCS) were the most favorable parameters. Optimized doped TCOs were obtained for 0.5 M % Hf-doped In2O3 when produced at 400 ˚C, showing high transparency in the visible range of the spectrum, a bulk resistivity of 5.73 × 10-2 Ω.cm, mobility of 6.65 cm2 /Vs and a carrier concentration of 1.72 × 1019 cm 3 . Finally, 0.5 M % Hf-doped In2O3 thin films were annealed in rapid thermal annealing (RTA) for 10 min at 600 ˚C, obtaining better results than before achieving a bulk resistivity of 3.95 × 10-3 Ω.cm, mobility of 21 cm2 /Vs and carrier concentration of 7.98 × 1019 cm-3.